Molecular Identification of the Fusarium Verticillioides Isolated from Corn Grains from Karbala Province - Amoori Abd Ali, Hadeel; Imtair AlGaraawi, Neepal; W. Kadium, Suaad (Pure Sciences International Journal of Kerbala, 2024)
Cereals are an important source of nutrition for both people and their domestic animals. Whether in the field or in storage, these grains are sensitive to fungus infestation . Fusarium verticillioides is the most important one. The results of this study showed that this species was present in all grain samples obtained from diverse locations . By doubling the region of F. verticillioides, the study revealed the molecular diagnosis. The polymerase chain reaction (PCR) technology was used. The results of the molecular analysis showed that this strain was diagnosed for the first time in Iraq, as the results of the comparison of the sequence of the nitrogenous bases of isolate No. 1 showed that it was 99% identical to the isolate registered in Australia under ID: KP132240.1, which belonged to the type F. verticillioides. The results of the alignment also showed that there was a discrepancy at position 390, as the nitrogenous base Guanine was recorded in the sequences of the isolate under study instead of the Adenine nitrogenous base (A) and this variation was of the type of Transition (equivalent substitution). Transmutation of the two laws is of the non-equivalent substitution type Transvertion, and that this type was registered under the accession number DI: OP056029.